Randomized, Placebo‐Controlled, Double‐Blind 8‐Week Trial on the Efficacy of A Proprietary Kiwifruit Extract on Constipation‐Predominant Irritable Bowel Syndrome - Holtmann, Gerald; Talley, Nicholas J.; Nandurkar, Sanjay; Gibson, Peter R. (JGH open, 2025)
ABSTRACT Background Green kiwifruit (Actinidia deliciosa var Hayward) extract improves constipation. This study aimed to determine its efficacy in patients with constipation‐predominant irritable bowel syndrome (IBS‐C). Methods A randomized, multicenter, double‐blind, parallel‐group, placebo‐controlled trial was conducted in 186 IBS‐C patients (Rome III criteria). Patients received either placebo or kiwifruit extract (575 mg twice daily for 4 weeks, followed by 575 mg daily for 4 weeks). Outcomes included measures of bowel movement frequency, Bristol Stool Scores, and abdominal pain and related measures (100 mm visual analog scale). The primary efficacy end point was the combined improvement of the number of complete spontaneous bowel movements and reduction of weekly average abdominal pain symptom score by at least 30% for at least half of the weeks during treatment. Results On kiwifruit extract, the proportion of subjects with increased frequency of spontaneous bowel movements (54% vs. 36%, p = 0.012), improved Bristol Stool Score (87 vs. 73%, p = 0.014), and abdominal pain (74% vs. 59%, p = 0.023) was greater than in controls. However, no difference was observed in the combined two‐variable primary end point (24% vs. 26%; p = 0.798). In post hoc analyses of 49 subjects with severe pain (≥ 50 mm), kiwifruit extract improved the primary end point (33% vs. 8%, p = 0.028) and normalized or maintained normal bowel actions with kiwifruit extract (44% vs. 24%, p = 0.005). Conclusions In patients with IBS‐C, kiwifruit extract improves bowel habits and abdominal pain. The predefined end point for the whole study population was not met because the 30% or greater improvement of pain only occurred in patients with more pain. Trial Registration Australian Clinical Trial Research Network (ACTRN 12613001222730)